PLURALITAS METODE PEMBERIAN SUARA: DISHARMORNI TRADISI LOKAL DALAM MEWUJUDKAN INKLUSIVITAS PEMILU - Devi Darmawan (Jurnal Dinamika Hukum, 2014)
Procedural rules of electoral law require the application of the principle of equality in the electoral process. Ironically, The Constitutional Court has created the plurality law about voting methods in electoral districts through a legalized traditional value of the local society. The problematic appears when its methods couldn’t fulfill the principle of democratic elections and also increase the potency to set the electoral law at deviance, especially in the voting stage. Therefore, without any intention to neglect the existence of traditional local cultures, this paper will explain the relevance of plurality law about voting methods towards creating the inclusiveness in an election process.Keywords: Democratic Electoral, Plurality Law, Voting Methods